Telecommunications Policy: An evaluation of 40 years' research history - Youngsun Kwon; Joungwon Kwon (International Telecommunications Society (ITS), 2017)
Telecommunications Policy (TP) marked its 40-year milestone in 2016. At this juncture of 40-year milestone, this paper implements a text analysis with keyword frequency data derived from the abstracts of papers published for the past 40 years to take a look at the big picture of key concepts that constitute research subjects of the journal. With keywords and bibliographic data, this paper calculates key research indexes to overview dynamically changes in research focuses in the journal. This paper found that the difference in research performance across research subjects within three continents has declined over time, even though still there exist wide differences in research performance across subjects within nations, and the mid-1990s marked a watershed dividing the 40-year history into two parts.
Keywords: 330; Telecommunications policy; Key research area; Key research index; Theil index; Text analysis; Bibliographic analysis